A Memory of the Southern Seas : 1904 - Becke, Louis, 1855-1913 (Salt Lake City, UT : Project Gutenberg, 2008)
"A Memory of the Southern Seas" by Louis Becke is a narrative collection of stories set against the backdrop of the South Seas, written in the early 20th century. The opening portion focuses on various characters and accounts related to seafaring life, particularly highlighting the notorious figure of Captain "Bully" Hayes, known for his tumultuous nature and the colorful tales that surround him. Through anecdotes and observations about life at sea, the work delves into themes of adventure, morality, and the complexities of human nature. At the start of the book, Becke introduces Captain Hayes, providing a sketch of his life intertwined with historical figures like missionary James Chalmers. The narrative recounts Hayes$1 (Bs reputation and the myths that fuel his legendary status. It describes a series of encounters, shedding light on his interactions with missionaries and his unpredictable temperament, while also juxtaposing humor and darker undertones of his exploits. Through this vivid portrayal, readers begin to grasp the chaotic yet engaging world of the Southern Seas and the larger-than-life characters that inhabit it, setting the stage for future stories that explore other facets of maritime life. (This is an automatically generated summary.)s
Captain "Bully" Hayes -- The "whale cure" -- The sea "salmon" season in Australia -- "Jack Shark" -- Some Pacific Islands fishes -- "Luck" -- Bull-dogs of the sea -- "Revenge" -- Saunderson and the dynamite -- The stealing of Sa Luia.
From: Chinkie's Flat and Other Stories.
Release date is 2008-03-11
Produced by David Widger
Keywords: Short stories; Pacific Area -- Social life and customs -- Fiction; South Pacific Ocean -- Fiction